Prediksi Harga Cryptocurrency (Bitcoin) Menggunakan Model ARIMA - Mega Dewi Sri Utami; Revalina Aurelia Oktanti; Muhammad Rifki; Achmad Budi Susetyo (PT Syamilah Literasi Islami, 2025)
Bitcoin, a leading cryptocurrency, exhibits high volatility influenced by global regulations, impacting financial stability in developing nations like Indonesia, where it is recognized as a commodity by BAPPEBTI rather than legal tender. This study aims to predict Bitcoin prices using the ARIMA model on monthly historical data from January 2023 to December 2024, addressing gaps in simple, accurate forecasting for novice investors. Quantitative time series analysis involved Augmented Dickey-Fuller (ADF) stationarity tests (non-stationary at level, stationary after first differencing), ARIMA parameter identification via ACF/PACF, model stability (inverse roots within unit circle), and residual diagnostics (Ljung-Box confirming white noise). Results show a gradual upward price trend for 2025 with wide confidence intervals reflecting inherent volatility, validating ARIMA's effectiveness for short-term predictions using EViews 12.